Development Of DNA-Based Diagnostic Tests For The Detection Of Shigella Dysenteriae, Shigella Flexneri And Shigella Sonnei - Shakrin, Nik Noorul Shakira Mohamed (2010)
Shigellosis or bacillary dysentery caused by Shigella spp. remains as significant health problem worldwide. Current detection and identification methods of the pathogens from stool specimens by culture method is relatively insensitive, generally time consuming (~ 2-5 days) and laborious. In this study, thermostabilised Polymerase Chain Reaction (PCR) assays were developed for the detection of ompA genes in Shigella dysenteriae, Shigella flexneri and Shigella sonnei. The tests contained specific primers for the detection of S. dysenteriae, S. flexneri and S. sonnei respectively, freezed-dried or thermostabilised PCR reagents with Internal Control (IC) and gel loading dye.